The Influence of Brand Image and Service Quality on Outpatient Satisfaction Of RSAU dr. M Hassan Toto - Rike Devi Khomala; Oci Etri Nursanty (Manunggal Halim Jaya, 2026)
Brand image is a representation of the overall perception of a brand formed from past information and experiences. In the context of health services, patients' perceptions of the quality of service are greatly influenced by the comfort, friendliness of the officers, and the experience of the service received. This study aims to analyze the influence of brand image and service quality on patient satisfaction. The method used is quantitative research with a cross-sectional approach. The sampling technique used probability sampling with a total of 98 respondents. Data analysis was carried out using multiple linear regression. The results showed that brand image and service quality had a positive and significant effect on patient satisfaction with a significance value (0.000 < 0.05). The conclusion of this study shows that improving brand image and service quality together can increase patient satisfaction.